Mechanical and matrix effects of short and long-duration exposure to beta-aminopropionitrile in elastase-induced model abdominal aortic aneurysm in mice - Pete H. Gueldner, BS; Ande X. Marini, BS; Bo Li, MD, MS; Cyrus J. Darvish, BS; Timothy K. Chung, PhD; Justin S. Weinbaum, PhD; John A. Curci, MD; David A. Vorp, PhD (JVS - Vascular Science, 2023)
Objective: Evaluate the mechanical and matrix effects on abdominal aortic aneurysms (AAA) during the initial aortic dilation and after prolonged exposure to beta-aminopropionitrile (BAPN) in a topical elastase AAA model. Methods: Abdominal aortae of C57/BL6 mice were exposed to topical elastase with or without BAPN in the drinking water starting 4 days before elastase exposure. For the standard AAA model, animals were harvested at 2 weeks after active elastase (STD2) or heat-inactivated elastase (SHAM2). For the enhanced elastase model, BAPN treatment continued for either 4 days (ENH2b) or until harvest (ENH2) at 2 weeks; BAPN was continued until harvest at 8 weeks in one group (ENH8). Each group underwent assessment of aortic diameter, mechanical testing (tangent modulus and ultimate tensile strength [UTS]), and quantification of insoluble elastin and bulk collagen in both the elastase exposed aorta as well as the descending thoracic aorta. Results: BAPN treatment did not increase aortic dilation compared with the standard model after 2 weeks (ENH2, 1.65 ± 0.23 mm; ENH2b, 1.49 ± 0.39 mm; STD2, 1.67 ± 0.29 mm; and SHAM2, 0.73 ± 0.10 mm), but did result in increased dilation after 8 weeks (4.3 ± 2.0 mm; P = .005). After 2 weeks, compared with the standard model, continuous therapy with BAPN did not have an effect on UTS (24.84 ± 7.62 N/cm2; 18.05 ± 4.95 N/cm2), tangent modulus (32.60 ± 9.83 N/cm2; 26.13 ± 9.10 N/cm2), elastin (7.41 ± 2.43%; 7.37 ± 4.00%), or collagen (4.25 ± 0.79%; 5.86 ± 1.19%) content. The brief treatment, EHN2b, resulted in increased aortic collagen content compared with STD2 (7.55 ± 2.48%; P = .006) and an increase in UTS compared with ENH2 (35.18 ± 18.60 N/cm2; P = .03). The ENH8 group had the lowest tangent modulus (3.71 ± 3.10 N/cm2; P = .005) compared with all aortas harvested at 2 weeks and a lower UTS (2.18 ± 2.18 N/cm2) compared with both the STD2 (24.84 ± 7.62 N/cm2; P = .008) and ENH2b (35.18 ± 18.60 N/cm2; P = .001) groups. No differences in the mechanical properties or matrix protein concentrations were associated with abdominal elastase exposure or BAPN treatment for the thoracic aorta. The tangent modulus was higher in the STD2 group (32.60 ± 9.83 N/cm2; P = .0456) vs the SHAM2 group (17.99 ± 5.76 N/cm2), and the UTS was lower in the ENH2 group (18.05 ± 4.95 N/cm2; P = .0292) compared with the ENH2b group (35.18 ± 18.60 N/cm2). The ENH8 group had the lowest tangent modulus (3.71 ± 3.10 N/cm2; P = .005) compared with all aortas harvested at 2 weeks and a lower UTS (2.18 ± 2.18 N/cm2) compared with both the STD2 (24.84 ± 7.62 N/cm2; P = .008) and ENH2b (35.18 ± 18.60 N/cm2; P = .001) groups. Abdominal aortic elastin in the STD2 group (7.41 ± 2.43%; P = .035) was lower compared with the SHAM2 group (15.29 ± 7.66%). Aortic collagen was lower in the STD2 group (4.25 ± 0.79%; P = .007) compared with the SHAM2 group (12.44 ± 6.02%) and higher for the ENH2b (7.55 ± 2.48%; P = .006) compared with the STD2 group. Conclusions: Enhancing an elastase AAA model with BAPN does not affect the initial (2-week) dilation phase substantially, either mechanically or by altering the matrix content. Late mechanical and matrix effects of prolonged BAPN treatment are limited to the elastase-exposed segment of the aorta. Clinical Relevance: This paper explores the use of short- and long-term exposure to beta-aminopropionitrile to create an enhanced topical elastase abdominal aortic aneurysm model in mice. Readouts of aneurysm severity included loss of mechanical stability and vascular extracellular matrix composition reminiscent of what is seen in the course of human disease. Additionally, we show that the thoracic aorta, unlike the findings below the renal arteries, is not damaged in our animal model.